Effects of Vegetation on the Transport of Dune Sand - Buckly, Ralf (Annals of Arid Zone, 2016)
The movement of wind blown sand on partially vegetated surfaces, and its consequences for the morphodynamics of sand dunes and the rehabilitation of eroded areas, is still significantly less studied than transport processes on bare sand. Currently, there are a number of parallel lines of research which do not always overlap or mesh. These are: theoretical calculations; improved instrumentation for field and wind-tunnel use, including reptation traps; fixed wind-tunnels, largely for testing new theoretical development: portable wind tunnels, largely for measuring erosion potential; sediment transport in agricultural crops and fallow areas; macro-scale erosional processes over large areas; stabilization and destabilization; analyses of patterns, trends and causative factors for current dune morphology, planforms and migration; historical and palaeontological analyses of past dunefields; coastal dune studies; dust mobilization and transport studies; and analyses of dunefield vegetation dynamics. For sparsely vegetated sand dunes, the Buckley modification of Bagnold’s bare-sand transport equation, derived from wind tunnel experiments a decade ago, does not appear to have been either superseded or adequately tested in the field. Many alternative formulations have been proposed for different scales and circumstances, but none applies generally.